Evaluating the effectiveness of the optimized cryptographic system Gentry of conditions for ensure the confidentiality of information - Ільєнко, А. В. (Science-based technologies, 2017)
The paper first defined the peculiarities of the optimized cryptographic Gentry. The analysis of existing homomorphic encryption of information systems and on the basis of the analysis highlighted the advantages and disadvantages of modern algorithms. As a result of identified features of the application of homomorphic cryptosystems, while ensuring the integrity and confidentiality of information resources, their classification and properties. The analysis allowed to generate further ways to optimize cryptographic algorithm Gentry, as well as his use of in the implementation of cloud computing. Optimized algorithm Gentry provides significantly greater cryptographic strength due to additional encryption of the session key. The efficiency of the optimized cryptographic method Gentry of the conditions to ensure confidentiality of the information was based on the international standard ISO 14756 «Information technology. Measurement and rating performance evaluation software systems».